PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN DENGAN EKUITAS MEREK SEBAGAI VARIABEL MODERASI (Survei pada Pembeli Handphone Samsung Android di Matahari Singosaren Surakarta) - Geger Aji Nugroho, SL Triyaningsih & Edi Wibowo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this research was to analyze: 1) the effect of product quality on customer satisfaction 2) the effect of brand equity on consumer satisfaction 3) the effect of product quality on customer satisfaction with the brand equity as a moderating variable. This study is a survey on consumer handphone Samsung in the Matahari Singosaren Plaza. The research sample of 100 people with sampling used purposive sampling and accidental sampling. The technique of collecting data used questionnaires. Data were analyzed used multiple linear regression and test of absolute difference. The results showed that the product quality has significant effect on consumer satisfaction Samsung android. Brand equity has significant effect on consumer satisfaction Samsung android. Brand equity does not moderate the effect of product quality on customer satisfaction Samsung android.Keywords: product quality, brand equity, consumer satisfaction.